Studies towards the synthesis of novel tridentate ligands for use in ruthenium metathesis catalysts - Millward, Tanya (Rhodes University, Faculty of Science, Department of Chemistry, 2009)
This work has focussed on the preparation of a variety of tridentate ligands, designed to form ruthenium complexes as potential metathesis catalysts. Various approaches to the tridentate, malonate-tethered imidazolidine system have been investigated, and a promising route to accessing ligands of this type is discussed. A tridentate malonate-tethered pyridine ligand has been successfully prepared and its dithallium salt has been accessed by hydrolysis with thallium carbonate; approaches to a longer-chain analogue have also been investigated. A thallium pyridine-2,6- dicarboxylate ligand has been has been successfully prepared, as have a range of pyridine diamine ligands, with various alkyl and aromatic substituents on the amine donor atoms. Preliminary investigations into the potential of these compounds as ligands for alkylidene ruthenium complexes are reported using molecular modelling techniques. The geometries and steric energies of the ligands and their corresponding complexes have been analysed, and results obtained from two different software packages are compared. Finally, some preliminary complexation studies have been undertaken.
Keywords: Ligands; Catalysis; Metathesis (Chemistry); Ruthenium; Complex compounds